2022
DOI: 10.21037/apm-22-165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anemia during the third trimester of pregnancy on postpartum depression and pregnancy outcomes in pregnant women older than 35 years: a retrospective cohort study

Abstract: Background: There is no study on the impact of anemia on postpartum depression and outcomes in mothers older than 35 years, which makes the nursing of these pregnant women with anemia more difficult. Methods:We retrospectively collected the demographic and clinical characteristics of pregnant women older than 35 years at conception between August 2014 and December 2019. Hemoglobin less than 110 g/L was defined as anemia. Postpartum depression was assessed according to Edinburgh Postnatal Depression Scale. A su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Various studies reported an increased risk of foetal growth retardation, low birth weight, small for gestational age infants, 5–7 low APGAR score, as well as cognitive and behavioral abnormalities later in life 7,8 . Anemia that newly occurs in the third trimester of pregnancy is associated with less severe but not negligible consequences including: increased blood loss at delivery, increased risk of prolonged labor and caesarean section 9–11 . Postpartum sequelae include anemia, mood disorders, and decreased lactation 12,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies reported an increased risk of foetal growth retardation, low birth weight, small for gestational age infants, 5–7 low APGAR score, as well as cognitive and behavioral abnormalities later in life 7,8 . Anemia that newly occurs in the third trimester of pregnancy is associated with less severe but not negligible consequences including: increased blood loss at delivery, increased risk of prolonged labor and caesarean section 9–11 . Postpartum sequelae include anemia, mood disorders, and decreased lactation 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Anemia that newly occurs in the third trimester of pregnancy is associated with less severe but not negligible consequences including: increased blood loss at delivery, increased risk of prolonged labor and caesarean section. [9][10][11] Postpartum sequelae include anemia, mood disorders, and decreased lactation. 12,13 All these factors result in an overall greater maternal and foetal morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%